Refugee Students Views about the Problems They Face at Schools in Turkey - Gömleksiz, Mehmet Nuri; Aslan, Sibel (Mustafa ÖZMUSUL, 2018)
The aim of this study is to determine secondary refugee students’ views about the problems they faced at Turk schools. In this direction, the refugee students’ views about methods & and techniques the teachers used in the class; school culture, rules, interaction, problems they have with their school friends; and the support of their families were determined. Moreover, their views about the school subjects, content, gains and necessity of these subjects;  their competence in using Turkish; and their previous education’s effect on their current education were determined. In this study, qualitative research design was used. The study group consisted of the refugee students enrolled at two state schools in Elazığ city center in 2017-2018 academic year, second term. Maximum variation sampling method was used in the study. In determination of school, whether there are refugee students or not at that school was considered. From each school eight refugee students  were selected and totally 16 refugee students were included in the study. In determination of these students, the views of headmaster and deputies head of the secondary school and teachers were considered. Volunteer refugee students participated to the study. A semi-structured interview form, which was designed by the researcher was used for data collection. Six semi- structured questions were asked to identify refugee students’ views about the problems they faced. These questions were reviewed by a professor and two assistant professors. The clarity of questions were negotiated with three secondary school teachers. With refugee students whom do not know any Turkish or English, the interview had through a translator. Study results revealed that refugee students have some problems at Turk schools because of several reasons like medium of instruction, courses contents, the lack of family support, school culture- rules, and methods& techniques teachers used. Several recommendations are offered based on the research findings.